Derive three equation of motion

Asked by  | 22nd Oct, 2013, 01:29: PM

Expert Answer:

(1) First equation of Motion: v = u + a t

Consider a body of mass “m” having initial velocity “u”.

Let after time “t” its final velocity becomes “v” due to uniform acceleration “a”.

Now we know that:
Acceleration = Change in velocity / Time taken

Acceleration = (Final velocity - Initial velocity) / Time taken

  a = v - u / t
 a t = v - u

or  v = u + a t

This is the first equation of motion.


(2) Second equation of motion: s = u t + 1/2 at2

Let the distance travelled by the body be “s”.

We know that
Distance = Average velocity x Time

Also, Average velocity = (u + v) / 2

.:  Distance (t) = (u + v) / 2 t            …….eq.(1)

Again we know that:

v = u + at

Substituting this value of “v” in eq.(1), we get

s = (u + u + a t) / 2 t
s = (2 u + a t) / 2 t
s = (2 u t + a t2) / 2
s = (2 u t / 2) + (a t2 / 2)

or  s = u t + (1/2) a t2

This is the 2nd equation of motion.

 

(3) Third equation of Motion:  v2 = u2 +2 a s

We know that

v = u + a t
v - u = a t

or  t = (v - u) / a                                    ………..eq.(2)

Also we know that


Distance = average velocity x Time

.: s = [(v + u) / 2] x [(v - u) / a]

s = (v2 – u2) / 2 a

2 a s = v2 – u2

or  v2 = u2 + 2 a s

This is the third equation of motion.

 

Answered by Faiza Lambe | 23rd Oct, 2013, 04:57: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.